2006
DOI: 10.1299/jsmeb.49.205
|View full text |Cite
|
Sign up to set email alerts
|

Development and Verification of 3000 Rpm 48 Inch Integral Shroud Blade for Steam Turbine

Abstract: The 3 000 rpm 48 inch blade for steam turbine was developed as one of the new standard series of LP end blades. The new LP end blades are characterized by the ISB (Integral Shroud Blade) structure. In the ISB structure, blades are continuously coupled by blade untwist due to centrifugal force when the blades rotate at high speed. Therefore, the number of the resonant vibration modes can be reduced by virtue of the vibration characteristics of the circumferentially continuous blades, and the resonant stress can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Figure 10 shows the example of the wiring used in the recent field test of the last blade of the steam turbine. It is reported that no damage of the strain gage and the wiring was observed after the field test of around one month, and the valuable verification data was obtained (78) .…”
Section: History Of Technology On Measurement and Verification Testmentioning
confidence: 92%
See 1 more Smart Citation
“…Figure 10 shows the example of the wiring used in the recent field test of the last blade of the steam turbine. It is reported that no damage of the strain gage and the wiring was observed after the field test of around one month, and the valuable verification data was obtained (78) .…”
Section: History Of Technology On Measurement and Verification Testmentioning
confidence: 92%
“…Fig. 10 Blade with Strain Gauge (After Field Test) (78) Journal of System Design and Fig. 11 Campbell diagram of blade measured by non-contact measurement method (82)…”
Section: History Of Technology On Measurement and Verification Testmentioning
confidence: 99%
“…In order to make the rotating blade more reliable, the method of adding shrouds to the blade is often used to solve the problem in engineering. e shroud can increase the rigidity and the natural frequency of the blade, and when the blade is vibrating, the working surface of the shroud can rub against each other to absorb vibration energy [1]. e process of contact vibration with shrouded blades is very complex and usually includes separation-contact-stick-slip states, with typical nonlinear characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop the new LP end blades with high reliability, analysis methods for the vibration characteristics of the ISB structure were developed and their validity was confirmed before applying them to the blade design (2) (3) . Moreover, the final reliability of the developed blades has been confirmed by verification tests such as rotational vibration tests and actual loading tests, and these test results have been accumulated into the database (4) . The accuracy of the predicted frequency and the vibratory stress has been improved, using the database of the test results.…”
Section: Introductionmentioning
confidence: 99%